Effect of Operating Condition of Natural Dye Production from Red Spinach (Amaranthus Dubius ) using Solvent Extraction - Asdarina Yahya; Siti Nur Azeera Sulaiman; Maryudi Maryudi (ASEAN Journal of Chemical Engineering, 2024)
Due to synthetic dyes’ health and environmental impacts, there is a growing demand for natural dyes as a sustainable alternative. This study investigates the production of natural dye from red spinach (Amaranthus dubius) using solvent extraction methods. The dominant pigment, betacyanin, was extracted and analyzed under various operating conditions. The effects of different solvents (water, ethanol, acetone, ethanol-water, and acetone-water), extraction temperatures (20°C, 40°C, 60°C, and 80°C), and extraction times (30, 60, 90, and 120 minutes) on dye yield were evaluated. The highest yield of 34% was achieved using acetone water (50:50) at 60°C for 60 minutes. The extracted dyes were analyzed using a chroma meter. These findings suggest optimal conditions for maximizing dye yield from presenting a viable alternative to synthetic dyes at 60℃ and 60 minutes can get ca. 34% of yield. FTIR analysis showed that the extracted natural dye contains antioxidants compared with synthetic dye.